Ответы и объяснения

2012-05-20T09:03:26+04:00

26-5у=2-9у

-5у+9у=2-26

4у=-24

у=-5

 

9х+11=13х-1

9х-13х=-1-11

-4х=-12

х=3

 

12х+31=23х-2

12х-23х=-2-31

-11х=-33

х=3

 

2(х-2)-1=5(х-2)-7

2х-4-1=5х-10-7

2х-5х=-10-7+4+1

-3х=-12

х=4

 

у+20=-у

у+у=-20

2у=-20

у=-10 

2012-05-20T09:39:41+04:00

26-5у=2-9у

-5у+9у=2-26

4у=-24

у=-5

 

9х+11=13х-1

9х-13х=-1-11

-4х=-12

х=3

 

12х+31=23х-2

12х-23х=-2-31

-11х=-33

х=3

 

2(х-2)-1=5(х-2)-7

2х-4-1=5х-10-7

2х-5х=-10-7+4+1

-3х=-12

х=4

 

у+20=-у

у+у=-20

2у=-20

у=-10